First record of Phloeophila (Orchidaceae: Pleurothallidinae) for the Flora of Mexico - López Velázquez, Guillermo; Solano Gómez, Rodolfo; Pérez-Farrera, Miguel Ángel (Instituto de Ecología, A.C., 2007)
Phloeophila peperomioides is a Central American orchid and its presence in Mexico was expected. Specimens collected recently in Chiapas allow us to report for the first time the existence of this species and its genus as part of the Mexican flora. Currently Phloeophila is recognized as a different genus from Pleurothallis, where it had been formerly included. Here we describe and illustrate the species from plants collected in Chiapas.